RELEVANSI NILAI SERTA IMPLIKASI RISIKO ATAS KEUNTUNGAN DAN KERUGIAN PERUBAHAN NILAI WAJAR KEWAJIBAN PERBANKAN DI INDONESIA - Faizal Irany Sidharta; Dewa Ayu Diah Pramiari (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2019)
This study aims to examine the influence of gains and losses on changes in fair value of debt instruments, EPS, and earnings after gain/loss on change in value of debt instruments on stock returns. This study also aims to examine the influence of net income after gains/losses of changes in the fair value of debt instruments and net income to beta return. Analyses were conducted on 23 foreign exchange banks since these foreign exchange banks are company that has public significant accountability and listed on the Indonesia Stock Exchange. This study used two models which were analyzed by multiple linear regression analysis. The first regression results found that gains/losses on changes in the value of debt instruments, net income after gain/ loss on change in fair value of the debt instrument, and EPS simultaneously affect stock returns. However, only EPS that has partial and positive effect on stock returns. The second regression results found that net income after gain/loss on change in fair value of debt instruments and net income of the current year has no simultaneous effect to the beta return, while net income for the year partially and positively affect the beta return.